Influence of pre-pregnancy body mass index and gestational weight gain on the results of bioelectrical impedance analysis as well as body weight changes in the post-partum period - Kamiński, Maciej; Grzesik, Paulina; Ceberak, Monika; Kimber-Trojnar, Żaneta; Patro-Małysza, Jolanta; Leszczyńska-Gorzelak, Bożena (Journal of Education, Health and Sport, 2018)
Introduction and the aim: There has been an alarming rise in the incidence of overweight and obesity worldwide. The prevalence of maternal obesity has more than doubled from 7.6 to 15.6% over the last two decades. The aim of the study is to compare findings of the bioelectrical impedance analysis (BIA) and body weight changes during 5-6 months after delivery depending on gestational weight gain (GWG) as well as pre-pregnancy body mass index (PPBMI). Material and methods: The study participants (76 mothers) were divided into groups according to PPBMI and GWG: 1. group (n=59) - PPBMI<24.9 kg/m2 2. group (n=17) - PPBMI ≥25 kg/m2 1’ group (n=41) - normal GWG 2’ group (n=35) - excessive GWG The methodology includes the results of questionnaires conducted among mothers in the early post-partum period and several months after delivery. Maternal body composition and hydration status were assessed by the BIA method at 48-72 hours after delivery. Statistical analysis was performed using the Mann-Whitney, χ2 test, and cross tabulation. A p-value ≤0.05 was considered statistically significant. Results: Lower fat tissue index (13,8 vs. 18,9; p<0,0001), adipose tissue mass (33,8 vs. 53,2; p<0,0001), and total body water (32,0 vs. 37,5; p< 0,001) as well as larger related free fat tissue mass (49,7% vs. 39,5%; p<0,001) were observed in the group of patients with PPBMI<24,9 kg/m2. Lower fat tissue index (11,9 vs. 18,2; p<0,001), adipose tissue mass (33,0 vs. 43,3; p<0,0001), total body water (31,2 vs. 35,5; p<0,01) and neonatal birth weight (3132,6 g vs. 3575g;p<0,01) were observed in the group of patients with normal GWG. Conclusions: The BIA method is a standardized technique, which is non-invasive, fast and well tolerated by patients. It seems to be capable to serve as a valuable tool in the assessment of maternal body composition and hydration status.